2016
DOI: 10.4315/0362-028x.jfp-16-057
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inoculation Procedures on Variability and Repeatability of Salmonella Thermal Resistance in Wheat Flour

Abstract: Limited prior research has shown that inoculation methods affect thermal resistance of Salmonella in low-moisture foods; however, these effects and their repeatability have not been systematically quantified. Consequently, method variability across studies limits utility of individual data sets and cross-study comparisons. Therefore, the objective was to evaluate the effects of inoculation methodologies on stability and thermal resistance of Salmonella in a low-moisture food (wheat flour), and the repeatabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…The Syamaladevi et al (24) experiment was similar to this study, except for the inoculum preparation. These results support the premise that inoculation procedures impact thermal resistance of Salmonella in wheat flour (10).…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…The Syamaladevi et al (24) experiment was similar to this study, except for the inoculum preparation. These results support the premise that inoculation procedures impact thermal resistance of Salmonella in wheat flour (10).…”
Section: Resultssupporting
confidence: 83%
“…0.05) and were lower than the other product types because the inoculum contained fewer cells. However, prior results have shown that initial inoculation level does not affect thermal resistance of Salmonella Enteritidis PT 30 in low-moisture products (10); therefore, comparisons of thermal resistance between pre-and postfabrication samples should not be affected by these differences in initial population.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Therefore, in this study we used a cocktail of 5 different EHEC strains of each serogroup to better account for the possible natural variability among strains (25). The inoculation method may influence the thermal resistance and survival of inoculated bacteria in challenge food studies (26). Liquid inoculation was reported to result in instability of Salmonella during equilibration, which can be expected since desiccation is an environmental stress adversely affecting viable bacterial numbers (27).…”
Section: Resultsmentioning
confidence: 99%